Production Of Cellulase By Trichoderma Sp. Pro-A1 And Bacillus Cereus B1 Using Palm Kernel Cake (Pkc) In Solid-State Fermentation - Lah, Tengku Norsalwani Tuan (2013)
Palm kernel cakes, waste from oil palm processing are potential fiber source for human diets. However, the cellulosic materials are indigestible and unsuitable for human consumption. Breaking the non-starch polysaccharides can make it more amenable as food additives. This research aims to investigate the use of fungus Trichoderma sp. Pro-A1 and bacteria Bacillus cereus B1 in breaking down the cellulosic materials in defatted and undefatted palm kernel cakes from the action of the cellulase inherent in these organisms using solid state fermentation (SSF). The SSF substrates were inoculated with three types of inocula of fungus Trichoderma sp. Pro-A1 which are mycelia biomass, conidia suspensions of varying concentrations (from solid culture) and fungal filtrate. B. cereus B1 inocula are cells from first seeding culture and cells from second seeding culture. Substrate particle size effect on cellulase activity was examined with sizes < 250 mm, ≥ 250 to <500 mm and ≥ 500 mm to < 1 mm. Maximum cellulase activity obtained by Trichoderma sp. Pro-A1 was about 5.95 FPU g-1 substrate for raw PKC and 10.77 FPU g-1 substrate for defatted PKC inoculated with 2 x 108spores/ml crude fungal filtrate. Cellulase activity was highest using 1 x 106 cells/ml of B. cereus B1 second seeding with 6.22 FPU g-1 substrate on defatted PKC and 2.15 FPU g-1 substrate on raw PKC. Higher cellulase activity achieved from sole inoculation with Trichoderma sp. Pro-A1 compared to either B. cereus B1 or combined. PKC particle size of 500 μm was best for the production of cellulase.